Modèles alternatifs de financement des investissements dans les infrastructures: Les perspectives offertes par les modèles de financement "innovants" - Andrew Meaney; Peter Hope (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2012)
– This paper examines the issue of financing infrastructure investment projects. It looks closely at what the market failures are that mean the private sector has not been able to cover the investment requirement itself. It will then assess the government failures associated with intervention, and identifies what public-private partnerships (PPPs) offer in overcoming these failures. The limitations of the PPPs are then addressed, and the regulated asset base (RAB) model is introduced as a potential alternative, with an assessment of its advantages and disadvantages.
Keywords: 330